History-Dependent Risk Preferences: Evidence from Individual Choices and Implications for the Disposition Effect. (22nd October 2019) - Andrikogiannopoulou, Angie; Papakonstantinou, Filippos
Abstract: Using trading data from a sports wagering market, we estimate individuals' dynamic risk preferences within a prospect theory paradigm. This market's experimental-like features facilitate preference estimation, and our long panel enables us to study whether preferences vary across individuals and depend on earlier outcomes. Our estimates extend support for experimental findings—mild utility curvature, moderate loss aversion, and probability overweighting of extreme outcomes—to a market setting and reveal that preferences are heterogeneous and history dependent. Applying our estimates to a portfolio choice problem, we show prospect theory can better explain the prevalence of the disposition effect than previously thought. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.